2012
DOI: 10.1111/ijfs.12012
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of volatile compound transformation in durian wine by nitrogen supplementation

Abstract: Summary This study evaluated the impact of added diammonium phosphate (DAP) and a L‐leucine‐L‐phenylalanine mixture (Leu+Phe) on durian wine fermentation by Saccharomyces cerevisiae var. bayanus EC‐1118. Changes in yeast cell population, oBrix, sugars, organic acids and pH were similar in all fermentations, regardless of nitrogen supplementation at a concentration of 150 mg N L−1. The supplementation of Leu+Phe accelerated the utilisation and reduced the formation of volatile sulphur compounds such as diethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…This indicated that the lychee juice was not deficient in nitrogen. These results were in agreement with some studies which showed that nitrogen supplementation in the form of amino acids (individually or mixture) did not have any effect on the rates of fermentation and the concentration of ethanol produced (Garde-Cerdan and AncinAzpilicueta, 2008; Lee et al, 2011Lee et al, , 2013. However, these data must be interpreted with caution and evaluated in relation to the nitrogen status of the juice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicated that the lychee juice was not deficient in nitrogen. These results were in agreement with some studies which showed that nitrogen supplementation in the form of amino acids (individually or mixture) did not have any effect on the rates of fermentation and the concentration of ethanol produced (Garde-Cerdan and AncinAzpilicueta, 2008; Lee et al, 2011Lee et al, , 2013. However, these data must be interpreted with caution and evaluated in relation to the nitrogen status of the juice.…”
Section: Discussionsupporting
confidence: 92%
“…Isocratic elution was performed for the sugars using a mobile phase consisting of acetonitrile and water (80:20 v/v) at a flow rate of 1.4 mL/min at 40°C with the methods of Lee et al (2013). Separation of glycerol was done using the same mobile phase at a flow rate of 0.5 mL/min at 30°C.…”
Section: Analysis Of Non-volatilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the formation of higher alcohols and their corresponding acetate esters is directly proportional to the quantity of amino acids added to the juice (Trinh et al, 2010;Lee et al, 2013). As reported by Chen et al (2014), supplementation of lychee juice with Phe resulted in significantly higher amounts of 2-phenylethyl alcohol, 2-phenylethyl acetate, 2-phenylethyl isobutyrate and 2-phenylethyl hexanoate.…”
Section: Introductionmentioning
confidence: 71%
“…the presence of BCAAs could attenuate the increased magnitude of 2-phenylethyl acetate caused by Phe addition. The level of 2-phenylethyl acetate was directly proportional to the quantity of Phe added to the must, and thus the increase in 2-phenylethanol accumulation (Lee et al, 2013). As a result, the reduction of 2-phenylethyl acetate in the mixed addition wines could be due to the lower level of 2-phenylethanol produced.…”
Section: Estersmentioning
confidence: 97%